Are the concerns of surgeons about cosmetic outcomes in pilonidal disease surgery more than necessary? - Dincer, Mürşit; Çıtlak, Gamze (My University, 2019)
Aim: Pilonidal disease is a chronic inflammatory process. From time to time poor cosmetic results can be obtained after surgery. In this study, it was aimed to investigate the effects of cosmetic results and the satisfaction level of the cases in patients who underwent surgery with different surgical techniques due to pilonidal disease.Material and Methods: The information about study was given to cases, which were operated due to pilonidal disease between January 2014 and December 2014 and could be contacted by phone. The questionnaire was applied to 125 cases who agreed to participate in the study. Cases were divided into two groups as primary excision with midline closure applied group and other surgical techniques applied group. The questions about the postoperative results were asked to the cases.Results: There was no statistically significant difference between the two groups in terms of pain duration, painless sitting-walking times, time to return to daily life, complications, reoperation rates and patient satisfaction of surgical scar. It was detected that there was more recurrence in the primary excision group and the results were statistically significant (p = 0.038). In the both groups, it was found that there is no statistically significant difference in the satisfaction questionnaire on surgical scar. (p> 0.05).Conclusions: The surgical scar can cause significant cosmetic problems in surgery treatment of pilonidal disease. Poor cosmetic results on cases may sometimes be more important. The results of this study showed that patients care more about the functional outcomes of treatment than the cosmetic results.
Keywords: Sağlık Bilimleri ve Hizmetleri; Cerrahi